Effect of different intensities of glycemic control on maternal and fetal outcome in women with diabetes in pregnancy - M, Laxmi Devi; Prasad, Madhav; Mukhtar, Lubna (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To compare the feto-maternal outcomes between patients who have achieved different glucose target values after intervention for hyperglycemia in pregnancy.Methods: A prospective comparative observational study was conducted in the Obstetrics Department of a Teaching Hospital. The main outcome parameters were the values of the fasting blood sugar (FBS) and the postprandial blood sugars (PPBS) obtained from the self-monitoring tests. The patients were grouped into two groups – the tight control group-I and less tight control group-II. maternal and neonatal parameters are compared. Pearson’s chi-square test was used for proportions and unpaired t-test was used for numbers after checking for normality of distribution and p-value of